Impacts of using an elastic fin on the phase change process under magnetic field during hybrid nanoliquid convection through a PCM-packed bed system - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2022)
In this work, combined utilization of an elastic fin and magnetic field on the phase change process dynamics is numerically assessed during nanoliquid convection in a phase change material (PCM)-packed bed embedded cylindrical reactor. Impacts of Reynolds number (Re between 100 and 700), elastic modulus of fin (between 10(4) and 10(9)), strength of the magnetic field (Ha between 0 and 100), length (between 0.2L and 0.6L) and vertical location (between 0.1H2 and 0.6H2) of the elastic fin on the phase change dynamics are numerically explored. Acceleration of the phase change process is observed by using an elastic fin as compared to a rigid one. The reduction of the phase completion time (t-pc) becomes 22.8% when cases at the highest and lowest Re are compared with flexible fin at the lowest elastic modulus. The magnetic field is effective when it is used with flexible fin of different size and for various vertical locations from the PCM zone. The reduction of the t-pc is obtained as 53% when cases with the lowest and highest vertical locations are compared in the absence of magnetic field while it is only 8.5% with magnetic field at the highest strength. Elastic fin with radially acting magnetic field provides an excellent contribution for controlling the phase change dynamics in a PCM-installed cylindrical reactor.
Keywords: Elastic fin; MHD; PCM; CFD; Hybrid nanofluid